PERANAN KEPALA DESA DALAM MENINGKATKAN PEMBANGUNAN INFRASTRUKTUR DESA DI DESA HILISERANGKAI KECAMATAN IDANOTAE KABUPATEN NIAS SELATAN - Parlindungan Marpaung (Jurnal Darma Agung, 2019)
This study discusses aboutCommunity Participation and Leadership Capability of the Village Head Against the Success of Development in Hiliserangkai Village, Idanotae Sub-District, South Nias Regency. Many problems often occur until now and one of them is the construction of inadequate infrastructure. The issue becomes an obstacle in the process of region’s progress and also hinders the progress of life, both in welfare, trade, agriculture, etc. This was due to the lack of attention from the government in the development and coordination of the regions. In addition, the community is not involved in the development program, but only involves certain people in the village. Theory and Concept of development and also the leadership capacity of the Village Head are inseparable in the success of development activities. The ability of the village’s leaderin the succedingvillage’s development is very important and central. This can help provide solutions in solving problems in the development process. These concepts and theories can be used as guidelines in implementing better and ideal development activities that aim for progress and mutual interests. The purpose of development is to provide a positive impact on the entire community which covers all aspects of life. The research method used in this study is a qualitative research method. The research method used in this research is a cauliflower research method and with 15 informants. The conclusion isthat the conditions of development, development programs, the ability of village leaders to fight for development are still not optimal and inadequate. In accordance with the results of the research, observations and data obtained from the research location, it can be said that the leadership capacity of the village’s leader has not been successful. In addition, the inhibiting factors both internally and externally also become obstacles in the process of development progress. Community response and forms of community participation are still very lack and wait the attention of the government only